KEBUTUHAN YANG DIRASAKAN PADA SOSIAL, EKONOMI, LINGKUNGAN PERMUKIMAN POLA ACAK KAWASAN PERKOTAAN KLATEN - Addina Adriana, Ahda; Marsoyo, Agam (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2024)
Population increase results in urban sprawl such as scattered settlements. Scattered settlements generally appear in areas with uneven topography such as mountains and rural, but in Klaten Regency they occur in urban areas with flat topography and the surrounding area is agricultural land with minimal availability of infrastructure. It is unique to research the felt needs by residents, including their social and economic needs. The aim of this research is to find felt needs of residents in scattered settlements in urban areas. The method used is a single case study method with data collection methods are in-depth interviews, questionnaires, and direct observation with explanatory qualitative descriptive analysis. The felt needs by residents in general are the availability of space and residential environment facilities such as economic and health facilities, access, social gathering spaces and privacy spaces. Specific needs based on the location are: locations near industry need water supplies and protective plants, locations near rice fields need good quality household waste water drainage channels, locations near the outskirts of the city need security facilities. It can be concluded that local governments must be firm in their development policies and developers must pay attention to the availability of settlement facilities.